Food sources of iodine in schoolchildren and relationship with 24-h urinary iodine excretion in Victoria, Australia. Issue 5 (14th March 2022) - Beckford, Kelsey; Grimes, Carley A.; Riddell, Lyann J.; Margerison, Claire; Skeaff, Sheila A.; Nowson, Caryl A.
Abstract: Dietary recalls have been used previously to identify food sources of iodine in Australian schoolchildren. Dietary assessment can provide information on the relative contributions of individual food groups which can be related to a robust objective measure of daily intake (24-h urinary iodine excretion (UIE)). In Australia, the government has mandated the use of iodised salt in breadmaking to address iodine deficiency. The aim of this study was to determine the dietary intake and food sources of iodine to assess their contribution to iodine excretion (UIE) in a sample of Australian schoolchildren. In 2011–2013, UIE was assessed using a single 24-h urine sample and dietary intake was assessed using one 24-h dietary recall in a convenience sample of primary schoolchildren from schools in Victoria, Australia. Of the 454 children with a valid recall and urine sample, 55 % were male (average age 10·1 (1·3 (sd ) years). Mean UIE and dietary iodine intake were 108 (sd 54) and 172 (sd 74) μg/d, respectively. Dietary assessment indicated that bread and milk were the main food sources of iodine, contributing 27 and 25 %, respectively, to dietary iodine. Milk but not bread intake was positively associated with UIE. Multiple regression (adjusted for school cluster, age and sex) indicated that for every 100 g increase in milk consumption, there was a 3 μg/d increase in UIE ( β = 4·0 (se 0·9), P < 0·001). In conclusion, both bread and milk were important contributors to dietary iodine intake; however, consumption of bread was not associated with daily iodine excretion in this group of Australian schoolchildren.